Contribution en azote de quatre legumineuses a la culture de mais - Haque, I.; Jutzi, S.C. (1985)
Reports on the Nitrogen contribution of one forage and three grain legumes, viz, vetch (Vicia villosa), wheat, faba beans, peas & lentils, to a subsequent maize crop in the Ethiopian highlands.